Mapping Landslide Susceptibility Areas Using GIS Analysis in Cilawu Sub-district, Garut, West Java - Nastiti, Afifa Ayu; Damayanti, Astrid; Maulidina, Kintan (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2023)
A landslide is the movement of soil mass down a slope. Landslides can be influenced by some factors including rainfall, soil type, land slope, land cover, and human activities. Cilawu Sub district, Garut, West Java is one of the most frequently experienced landslide areas which cause severe losses. This mapping aims to provide information about the landslide susceptibility areas in Cilawu Sub-district, Garut, West Java by using a Geographic Information System (GIS). This study used Digital Elevation Model (DEM) image, Landsat image, rainfall, geology, and soil types data which were then mapped using ArcGIS software. The analysis process used the overlay method, scoring method, and weighting method. The final result was a landslide map with 4 susceptibility levels covering low susceptibility, medium susceptibility, high susceptibility, and very high susceptibility. Based on this analysis, Cilawu District was dominated by the following classes: high susceptibility with an area of 5470.07 Ha, medium susceptibility with an area of 1627.78 Ha, very high susceptibility with an area of 515.96 Ha, and low susceptibility with an area of 366.16 Ha.